Food defense preparedness in small and very small meat and poultry establishments - Sobering, Lisa A. (My University, 2008)
Since the attacks of September 11, 2001, a heightened awareness to the threat of terrorism, particularly directed towards components of critical infrastructure, has permeated the nation. In May 2002, the United States Department of Agriculture Food Safety and Inspection Service issued general guidelines to assist meat and poultry establishments in strengthening their food defense efforts. The guidelines are voluntary; therefore, the extent of the industry’s implementation of these protective measures is mostly unknown. Furthermore, some have expressed concern that small and very small establishments may not be adequately prepared for an incident of intentional contamination of their products due to limited resources and other factors. A web-based survey was developed to gain insight into the opinions of establishments of varying size and geographic location within the United States on the importance of different food defense areas. The survey was circulated through four industry trade organizations: the North American Meat Processors Association, the American Association of Meat Processors, the American Meat Institute, and the Kansas Meat Processors Association. Members of these organizations represent various processing sectors and facility sizes. Employees (n=121) with knowledge of food defense preparedness activities of individual plants responded to the survey which was comprised of multiple choice, ranking, and yes or no questions. Questions ranged from demographic (e.g., size of establishment, geographic location) to ranking the likelihood of an intentional contamination event occurring in the U.S. Preliminary results showed that the majority of respondents represented federally inspected establishments (86%), establishments that were small in size (52%), and establishments that had some type of a food defense plan (74%). Fifty-one percent of respondents responded an intentional contamination event in the U.S. was somewhat likely; however, 66% of respondents indicated such an event was not likely to occur in their particular establishment. Additional data from this survey will be used to better understand the needs of small and very small processing establishments and to help guide development and delivery of effective food defense planning materials in the future.
Keywords: Food defense; Food safety; Food terrorism; Meat; Poultry; Food contamination; Agriculture, Food Science and Technology (0359)